EVALUASI IMPLEMENTASI TATA GUNA LAHAN BERKELANJUTAN DI WILAYAH PESISIR TELUK BENOA, BALI - Kadek Suardana; I Gusti Putu Anindya Putra; Ni G.A. Diah Ambarwati Kardinal (UNHI PRESS, 2020)
The Benoa Bay coastal area has an important role in terms of coastal and small island conservation, and has a value of production and recreation / tourism. Its strategic location at the center of business and tourism growth in South Bali has the potential to increase pressure on the region due to high land use. This study aims to understand in depth related to the use of sea and land space in the coastal area of Benoa Bay. This is done to find out the function of land, land use, and the implications of the application of spatial use policies in the Benoa Bay coastal area. This study uses a qualitative method with a library approach to regulations related to spatial planning that governs the Benoa Bay coastal area. Stages of analysis using a map overlay technique between land functions based on existing regulations and existing land cover based on remote sensing. From the research conducted, it was found that in general the main functions of the Benoa Bay coastal area are divided into 3 (three), namely: First, land space as a function of cultivation; Second, in the Ngurah Rai Tahura area as a protection function; and Third, in the aquatic space that functions as a culture. Unclear regulations related to the management of coastal areas in Benoa Bay in the form of Zoning Plans for Coastal Areas and Small Islands (RZWP3K) in the Province of Bali, causing legal uncertainty regarding the boundaries and functions of the Benoa Bay coastal area.